Identifikasi Kesalahan Siswa dalam Menjawab Pertanyaan dalam Memahami Konsep Matematika Sekolah Dasar Mengenai Bangun Datar - Unaenah, Een; Syafinka, Azayya; Anisa, Dela; Weningtyas, Zahra (Lembaga Yasin AlSys, 2023)
This study aims to identify students' mistakes in answering questions about the mathematical concept of flat shapes at the elementary school level. The background of this research is based on the important role of understanding mathematical concepts in learning and the importance of overcoming student mistakes to improve learning outcomes. The research instrument used was a written test containing several questions about the concept of flat shapes that had been compiled and validated by experts in mathematics education. The data collected from this test is then analyzed using statistical methods to identify patterns of errors that are often made by students. The results showed that most students experienced errors in understanding the concept of plane shapes, especially in recognizing the geometric properties of plane shapes and calculating their area and perimeter. Some common mistakes include incorrectly identifying the number of sides and angles in certain planes, mistakes in using the area and perimeter calculation formulas, and difficulties in understanding the relationship between different planes. This finding shows the important role of educators in understanding students' mistakes and developing appropriate teaching strategies to help students improve their understanding of the mathematical concept of flat shapes. The implications of the results of this study can be used as a basis for developing learning programs that are more effective in increasing students' understanding of mistakes in answering questions in understanding elementary school mathematics concepts regarding flat shapes.